Epidemiology of injuries in elite Korean handball athletes: a prospective cohort study - Roh, H. L.; Kim, C. W.; Park, K. J. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The aim of this study is to report injury patterns associated with training activities of South Korean elite handball athletes. METHODS: We prospectively collected data (stratified by sex, handball position, and injury location) on site from elite handball athletes between January and December 2019 at the Korea Training Center, South Korea. We used Chi2 tests and one-way analysis of variance to compare groups. Simple linear regression was conducted to determine associations between pain score and recovery time. RESULTS: We included 188 (96 male and 92 female) athletes who sustained 767 injuries (annual average, 4.08 injuries/athlete) during the study. Female athletes had a higher (P<0.001) injury incidence rate (6.21/1000 h) than male athletes (4.39/1000 h). Most injuries occurred in the lower extremities (50.2%). The injured body areas differed by handball position (P<0.001), and injury severity differed according to sex (P<0.001), with injuries in men typically resulting in a longer recovery time. Pain score and recovery time differed (both P<0.001) depending on the injured tissue type. Pain score was the highest and recovery time longest for ligament injuries; muscle injuries resulted in a high pain score but a relatively short recovery time. An increase in pain score of 1 was associated with an increase in recovery time of approximately 1.59 days. CONCLUSIONS: We believe that our data increase the understanding of the types and severity of injuries sustained by elite Korean handball athletes. These data should be incorporated into programs that aim to reduce the incidence of sports injuries and enhance athletic performance.